Adipose tissue aging partially accounts for fat alterations in HIV lipodystrophy. (31st December 2022) - Domingo, Pere; Giralt, Marta; Gavaldà-Navarro, Aleix; Blasco-Roset, Albert; Delgado-Anglés, Alejandro; Gallego-Escuredo, José Miguel; Gutiérrez, Maria Del Mar; Mateo, Maria Gracia; Cereijo, Rubén; Domingo, Joan Carles; Villarroya, Francesc; Villarroya, Joan
ABSTRACT: Lipodystrophy is a major disturbance in people living with HIV-1 (PLWH). Several systemic alterations in PLWH are reminiscent of those that occur in ageing. It is unknown whether the lipodystrophy in PLWH is the consequence of accelerated ageing in adipose tissue. We compared systemic and adipose tissue disturbances in PLWH with those in healthy elderly individuals (~80 y old). We observed similarly enhanced expression of inflammation-related genes and decreased autophagy in adipose tissues from elderly individuals and PLWH. Indications of repressed adipogenesis and mitochondrial dysfunction were found specifically in PLWH, whereas reduced telomere length and signs of senesce were specific to elderly individuals. We conclude that ageing of adipose tissue accounts only partially for the alterations in adipose tissues of PLWH.